Stakeholder Mapping Analysis on the Scaling-Up Nutrition Movement during the 1000 Days of Life between the Urban and Rural Government Areas (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
The Scaling-Up Nutrition (SUN) Movement was an intervention to overcome chronic malnutrition through integrated stakeholder collaboration. Furthermore, the roles of stakeholders' in the SUN-Movement were not optimal and their characteristics were not yet known based on the groups and government areas (cities and regency). This study aims to map the SUN-Movement stakeholders' roles in different groups and government areas based on their attitudes, powers, and interests. This is an observational descriptive research with a qualitative approach. Totally of 30 institutions as stakeholders were involved in this study and divided into 3 different groups, namely Decision Maker (DM), Provider (P), and Clients & Representatives (CR). The DM group have the power to influence programs. Also, the P group was better at handling technical issues, however, it cannot build collaboration with other stakeholders. The CR tend to build this collaboration passively, nevertheless, it does not consider the SUN-Movement to be important. Consequently, each stakeholder views their roles differently. Different perceptions about stakeholders' roles in various indicators and government areas reveals an implementation gap in the SUN-Movement. Therefore, in conclusion, strengthening advocacy, coordination, routine socialization, and communication between stakeholders could bridge the needs, constraints and challenges that cause malnutrition and stunting.